1997
DOI: 10.1086/304536
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength Monitoring of the BL Lacertae Object PKS 2155−304 in 1994 May. III. Probing the Inner Jet through Multiwavelength Correlations

Abstract: In May 1994 the BL Lac object PKS 2155-304 was observed continuously for ∼10 days with IUE and EUVE and for 2 days with ASCA, as well as with ROSAT and with ground-based radio, infrared, and optical telescopes. The light curves show a well-defined X-ray flare followed by a broader, lower amplitude extreme ultraviolet (EUV) flare ∼1 day later and a broad, low-amplitude UV flare ∼2 days later. X-ray fluxes obtained at three well separated times the preceding week indicate at least one previous flare of comparabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 38 publications
(29 reference statements)
7
79
2
Order By: Relevance
“…Its extreme TeV variability seems to demand an ultra-relativistic flow (bulk Lorentz factor ∼50) in at least portions of the jet that is believed to dominate the emission from this and other BL Lacs and blazars (Ghisellini & Tavecchio 2008). This BL Lac has been the target of several simultaneous multi-wavelength monitoring campaigns (e.g., Urry et al 1993;Brinkmann et al 1994;Edelson et al 1995;Courvoisier et al 1995;Urry et al 1997;Pian et al 1997;Pesce et al 1997;Foschini et al 2007Foschini et al , 2008. PKS 2155−304 is among the few blazars for which claims of an apparent QPO have been made, with UV and optical monitoring (from IUE) over five days possibly having a ∼0.7 d periodicity (Urry et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Its extreme TeV variability seems to demand an ultra-relativistic flow (bulk Lorentz factor ∼50) in at least portions of the jet that is believed to dominate the emission from this and other BL Lacs and blazars (Ghisellini & Tavecchio 2008). This BL Lac has been the target of several simultaneous multi-wavelength monitoring campaigns (e.g., Urry et al 1993;Brinkmann et al 1994;Edelson et al 1995;Courvoisier et al 1995;Urry et al 1997;Pian et al 1997;Pesce et al 1997;Foschini et al 2007Foschini et al , 2008. PKS 2155−304 is among the few blazars for which claims of an apparent QPO have been made, with UV and optical monitoring (from IUE) over five days possibly having a ∼0.7 d periodicity (Urry et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Edelson et al (1995) have reported correlated emission between X-ray, UV and optical emissions from PKS 2155-304 (an HBL BL Lac object). In another multi-wavelength campaign of PKS 2155-304 from 10 days data, Urry et al 1997 have reported X-ray flare leading EUV flare by one day and UV flare by two days. McComb et al (1995) and Maraschi et al (1999) have reported simultaneous X-ray and γ−ray flares in Mrk 421 in two different campaigns.…”
Section: Discussionmentioning
confidence: 98%
“…The multi-wavelength spectral energy distributions and variability time scales are used to probe the beaming parameters and the physical properties of the emitting regions, e.g., [48,76,125]. Correlated flares are sometimes measured across wavebands, giving support to the present of a dominant spatial region of emission, e.g., [124,131], but otherwise uncertainties of size scales, geometries, and parameters for the competing processes of energy loss and acceleration, often force the adoption of oversimplified or poorly-constrained models for individual jets.…”
Section: Cores: the Inner Jetsmentioning
confidence: 99%